2014
DOI: 10.1002/2014gl062065
|View full text |Cite
|
Sign up to set email alerts
|

Fresh exposures of hydrous Fe‐bearing amorphous silicates on Mars

Abstract: We have discovered relatively fresh exposures of a hydrated, amorphous material along the wall rock slopes in Coprates Chasma, Mars. Visible and near‐infrared reflectance spectra extracted from the deposits exhibit broad absorptions around 1.42, 1.94, and 2.25 µm that are most consistent with laboratory spectra of nanophase hydrated Fe‐rich allophane and Fe‐rich opal. The three absorptions, especially the 1.4 µm band, have the strongest hydration signatures yet detected on Mars by orbital data, suggesting high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 62 publications
2
13
0
Order By: Relevance
“…Reflectance bands for Fe-free allophane and imogolite in the mid-IR range (Figure 4) were also comparable to previous measurements on natural and synthetic allophane and imogolite samples (Bishop et al 2013;Weitz et al 2014). The addition of Fe in these materials resulted in overall darkening of the samples (Figure 4).…”
Section: Visible and Infrared Spectroscopysupporting
confidence: 87%
See 1 more Smart Citation
“…Reflectance bands for Fe-free allophane and imogolite in the mid-IR range (Figure 4) were also comparable to previous measurements on natural and synthetic allophane and imogolite samples (Bishop et al 2013;Weitz et al 2014). The addition of Fe in these materials resulted in overall darkening of the samples (Figure 4).…”
Section: Visible and Infrared Spectroscopysupporting
confidence: 87%
“…Poorly crystalline aluminosilicates such as allophane and imogolite have been identified on Mars using orbital infrared spectroscopy (Rampe et al 2012;Weitz et al 2014;Bishop and Rampe 2016). The presence of these nanophase (np) materials on Mars likely indicates a time when water was intermittent and/or too cold for formation of crystalline clays (Bishop et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of npWP on the martian surface has been previously inferred from orbital TES data (Rampe et al 2012) and CRISM data (Weitz et al 2014), in-situ Mössbauer spectroscopy (Morris et al 2006a(Morris et al , 2006b(Morris et al , 2008, a combination of in-situ APXS chemical data and Mössbauer spectroscopy (Clark et al 2005;Ming et al 2006), and in-situ TIR spectroscopy by mini-TES (Ruff et al 2011). MSL-CheMin XRD analyses confirm the presence of X-ray amorphous phases in all martian rocks and soil samples measured to date and indicate that amorphous phases are present in significant abundances Vaniman et al 2014;Morris et al 2015a).…”
Section: Implications For Martian Orbital and In-situ Analysesmentioning
confidence: 71%
“…Amorphous and poorly crystalline aluminosilicates have been identified from orbit at Mars 17,19,48 using the CRISM 49 and Thermal Emission Spectrometer 50 instruments. These studies found allophane and related poorly crystalline materials in several locations across the surface of Mars through modelling of Thermal Emission Spectrometer data 19 , Fe-rich allophane in isolated occurrences in Coprates Chasma 48 and poorly crystalline aluminosilicates in the topmost stratigraphical unit of the phyllosilicate-bearing outcrops at Mawrth Vallis 17 . The phyllosilicate stratigraphy at Mawrth Vallis contains several different units vertically through the profile 14,17 and is consistent with deposition, leaching or pedogenesis on the surface 7,51 .…”
Section: Characterization Of Amorphous and Poorly Crystalline Materiamentioning
confidence: 99%